Emerging Local Cable Television Services and Television Mobile Apps, and its impact on Cultural Transmission among the Badagar Community in the Nilgiri District, Tamil Nadu - R, Rajesh; Raja, G Balasubramania (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Since its beginning in India in 1959, the Television became the vital part of Indians life that reflected both cultivated cultural norms and values. Until the mid of the 1990s, the Indian television industry solely dominated by the government-owned Doordarshan television. However, the cable television services gained its reputation in India following the globalization of business in the 1990s, the audience found themselves with a vast number of choices. Like the Black Entertainment Television (BET) started at America in the 1980s dedicated to the interests of African American, the Badagas too have the cable television services emerged in the recent period to showcase the Badaga’s cultural values. At present, the discussion is whether these local Cable Television Services and Television Mobile Apps take the responsibility to promote precisely social and cultural values, and continues to transmit these values to the next generation. However, this article focus on the emergence and growth of local Cable Television Services and Television Mobile Apps, and its impact in transmitting the cultural value of Badagas from one generation to next generation. How to cite this article: Rajesh R, Raja GB. Emerging Local Cable Television Services and Television Mobile Apps, and its impact on Cultural Transmission among the Badagar Community in the Nilgiri District, Tamil Nadu. J Adv Res Jour Mass Comm 2018; 5(4): 104-108. DOI: https://doi.org/10.24321/2395.3810.201826